The Mexican Economics Science in the National System of Researchers and its Coverage in Web of Science and Scopus, 1982-2020 - Olivares-Vázquez, José Luis (2025)
The percentage of members of the Mexican National System of Researchers (SNI) in the field of economics with publications indexed in canonical commercial bibliometric databases (BCCs, Web of Science, and Scopus) was estimated for the periods 1982–1998, 1999–2015, and 2016–2020. Previous studies determined that the evaluation mechanisms for entering the system have undergone changes during these three periods, with the valuation of publications indexed in the CBBs increasing, which should be reflected in an increase in the presence of SNI authors in these databases. However, it has also been demonstrated worldwide that the social sciences in general are poorly represented in BCCs. The present results show that, in fact, the economic research of SNI members is represented in BCCs in proportions similar to those of the social sciences in several European countries, Canada, and Australia: around 40% in WoS and 50% in Scopus. A high percentage of Mexican researchers with publications in these databases who do not belong to the SNI were also found, in line with previous studies on the evolution of the Mexican academic profession in general, which reported a much higher percentage of full-time academics with scientific publications compared to the percentage of academics belonging to the system. The method of searching for SNIs in the BCCs developed for this study is an original implementation of the Author Name Disambiguation (AND) problem.